Introduction to value theory - Rescher, Nicholas (New York Prentice-hall, 1969)
A reprint of the popular 1969, Prentice-Hall edition, the principal innovation of this philosophical introduction to value theory is its focus upon values as they are dealt with in everyday life situations, and have sometimes been studied by sociologists and social psychologists, rather than upon value as has been standard in the philosophical tradition. The treatment of values is developed in the light of relevant work in the social sciences, particularly economics. The result is a book suitable as a textbook for upper-class and graduate courses in the theory of values and as supplementary material for both courses in normative ethics and foundations-oriented courses in economic theory.